Bladder paraganglioma managed with transurethral holmium laser resection: A case report. Issue 34 (27th August 2021) - Zhu, Xin; Zhou, Mi; Yu, Haitao; Kuang, Youlin; Chen, Yong; Li, Heqiu; Gou, Xin
Abstract: Rationale: Bladder paraganglioma is characterized by headache, palpitations, hypertension, blurred vision, or sweating during voiding. Transurethral holmium laser resection is a safe and efficacious alternative method for the resection of bladder neoplasms. Patient concerns: A 24-year-old female had a 2-year history of intermittent headaches, palpitation, and sweating during micturition. Diagnosis: Physical examination revealed a rise in the patient's blood pressure to 180/90 mmHg after micturition. Laboratory examination found that the blood catecholamine metabolites were significantly increased. Abdominal ultrasound and computed tomography (CT) scan indicated a 37 mm × 31 mm paraganglioma situated at the right anterolateral wall of the bladder. A diagnosis of bladder paraganglioma was considered based on a comprehensive evaluation of the physical examination, laboratory examination, ultrasound and computerized tomography scan. Interventions: Preoperative oral administration of a nonselective α-adrenergic receptor antagonist (phenoxybenzamine, 10 mg three times a day, ) accompanied by a high-sodium diet and generous fluid intake, was initiated 2 weeks before the surgery to stabilize intraoperative hemodynamics. As the patient was newly married and nulligravid, management with transurethral resection was considered superior to open or partial cystectomy and was selected as the treatment method. Outcomes: Transurethral holmium resection of the bladder paraganglioma was successfully performed with blood loss less than 20 ml and well-controlled intraoperative blood pressure. The 1-year follow-up results demonstrated well-controlled symptoms. Cystoscopy and evaluation of blood catecholamine metabolites revealed no disease recurrence. Lessons: Transurethral holmium laser resection is a good alternative approach for the resection of bladder paraganglioma, given its advantages of safety and efficacy.